Approaches for the Identification of Genetic Modifiers of Nutrient Dependent Phenotypes: Examples from Folate - Zinck, John W. R.; MacFarlane, Amanda J. (Frontiers in Nutrition, 2014)
By combining the sciences of nutrition, bioinformatics, genomics, population genetics and epidemiology, nutrigenomics is improving our understanding of how diet and nutrient intake can interact with or modify gene expression and disease risk. In this review, we explore various approaches to examine gene-nutrient interactions and the modifying role of nutrient consumption, as they relate to nutrient status and disease risk in human populations. Two common approaches include the use of SNPs in candidate genes to identify their association with nutritional status or disease outcomes, or genome wide association studies to identify genetic polymorphisms associated with a given phenotype. Here, we examine the results of various gene-nutrient interaction studies, the association of genetic polymorphisms with disease expression and the identification of nutritional factors that modify gene-dependent disease phenotypes. We have focussed on specific examples from investigations of the interactions of folate and B-vitamin consumption and polymorphisms in the genes of B vitamin dependent enzymes and their association with disease risk, followed by an examination of the strengths and limitations of the methods employed. We also present suggestions for future studies, including an approach from an on-going large scale study, to examine the interaction of nutrient intake and genotypic variation and their impact on nutritional status.